BOMB trial: First results of stereotactic radiotherapy to primary breast tumor in metastatic breast cancer patients - Ippolito, Edy; Silipigni, Sonia; Pantano, Francesco; Matteucci, Paolo; Carrafiello, Sofia; Marrocco, Maristella; Alaimo, Rita; Palumbo, Vincenzo; Fiore, Michele; Orsaria, Paolo; D’Angelillo, Rolando Maria; Altomare, Vittorio; et al. (Frontiers in Oncology, 2023)
Aim: a prospective dose escalation trial was developed to evaluate the maximum tolerated dose of stereotactic body radiotherapy (SABRT) to primary breast cancer in stage IV disease. The aim of the present report was to describe safety and outcome of the first dose level cohort of patients. Material and Methods: Patients with histologically confirmed diagnosis of invasive breast carcinoma (biological immuno-histochemical profile: luminal and/or HER2 positive) and distant metastatic disease not progressing after 6 months of systemic therapy with a tumor CT or 5FDG-PET detectable were deemed eligible. The starting dose was 40 Gy in 5 fractions (level 1) because this dose proved to be safe in previous dose-escalation trial on adjuvant stereotactic body radiotherapy. The maximum dose level was chosen as 45 Gy in 5 fractions. Dose limiting toxicity was any grade 3 or worse toxicity according to CTCAE v.4. Time-to-event Keyboard (TITE-Keyboard) design (Lin and Yuan, Biostatistics 2019) was used to find the maximum tolerated dose (MTD). MTD was the dose of radiotherapy associated with a ≤ 20% rate pre-specified treatment-related dose-limiting toxicity (DLT). Results: To date 10 patients have been treated at the starting dose level. Median age was 80 years (range 50-89). 7 patients had a luminal disease, while 3 patients had an HER2 positive disease. No patient suspended ongoing systemic treatment. No protocol defined DLTs were observed. Grade 2 skin toxicity occurred in 4 patients with diseases located close to or involving the skin. Median follow-up was 13 months and all 10 patients were evaluable for response: 5 achieved a complete response, 3 achieved a partial response and 2 showed a stable disease, all with a clinical benefit (resolution of skin retraction, bleeding and pain). The mean reduction in the sum of the largest diameters of target lesions was of 61.4% (DS=17.0%). Conclusions: SABR to primary breast cancer seems feasible and is associated with symptoms reduction. Continued accrual to this study is needed to confirm the safety and assess the MTD. Trial registration: ClinicalTrials.gov NCT05229575.